The Influence of Therapeutic Communication and Service Quality on Patient Loyalty at the Cardiology Poly of Sakinah Islamic Hospital at Mojokerto - Ferdiana Azhar; Prima Dewi Kusumawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
The form of service that is the main focus of the hospital includes outpatient services or poly services, including cardiac polyclinic. Outpatient poly services are the main focus because there are more patients in outpatient polyclinics than inpatients. But in fact there are still many patients who are less loyal to the hospital due to poor service, or the communication delivered by the officer is not acceptable to the patient. The purpose of this study was to analyze the influence of therapeutic communication and service quality on patient loyalty at the Cardiology poly of Sakinah Islamic Hospital at Mojokerto. The design of this research is analytic observational cross-sectional approach. The population of this study were all patients at the Cardiology poly of Sakinah Islamic Hospital at Mojokerto with an average of 1520 patients per month. Samples were taken by using simple random sampling technique as many as 304 respondents. Data were collected using a questionnaire instrument and tested with multiple linear regression. The results showed that partially and simultaneously independent variables (communication and service quality) affected the dependent variable (patient loyalty) which was indicated by a significance value = 0.000 < = 0.05 so that H1 was accepted, meaning that there was an influence between communication and service quality on patient loyalty. . This shows that the better the communication and service quality, the more loyal patients will be to the hospital.